Correlation of 25-Hydroxyvitamin D and Serum Lipid Levels Among Patients with Type 2 Diabetes - Muhammad Waqas, Hira Razzaq, Muhammad Akif Ali Khan, Sara Khan, Chaudhary Muhammad Arslan Khawar, Maheen Jamil, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We conducted this study among people with type 2 diabetes to see if 25-Hydroxyvitamin D and serum lipid levels correlate. Study Design: Retrospective/ Cross-sectional study Place and Duration: THQ Hospital Khairpur Tamewali, Bahawalpur. Jun 2021-Dec 2021 Methods: In this study, a total of 140 people with type-2 diabetes were examined. The patients ranged in age from 20 to 85 years. Detailed demographics, including age, sex, BMI, literacy, and occupation, were obtained from all patients with signed consent. Blood samples were obtained from each patient and sent to a facility to be analyzed. HbA1c and cholesterol levels were also tested. Serum 25(OH)D levels were determined using an electrochemiluminescence technique. The lipid panel was measured using an automated analyzer utilizing enzymatic techniques. SPSS 24.0 version was used to analyze complete data. Results: There were 80 (57.1%) males and 60 (42.9%) female patients in this study. Mean age of the patients was 49.12±3.61 years with mean BMI 27.11±8.44 kg/m2. 65 (46.4%) cases were literate and majority of the patients were job holders in factories 82 (58.6%). Frequency of vitamin D deficiency was found among 100 (71.4%) cases. Frequency of dyslipidemia was found among 108 (77.1%) patients. We found mean cholesterol level was 184.11±6.67 (mg/dl), mean HDL among patients were 45.16±5.53 mg/dl, mean triglyceride was 148.9±4.71 mg/dl, mean LDL among patients was 102.6±7.31 mg/dl and mean vitamin D deficiency among patients was 24.13±9.76 mg/dl. Conclusion: According to the findings of this study, vitamin D deficiency is extremely common among patients with type 2 diabetes. Furthermore, it is possible that vitamin D deficiency has an impact on dyslipidemia in patients with type 2 diabetes.